Page Kidney: Possible complication of renal biopsy. - Riaz, Muhammad Mohsin; Rizvi, Nabiha; Sabir, Omer; Rafique, Kashif; Manzoor, Shoaib (Pakistan Journal of Kidney Diseases, 2021)
Page kidney is an un-usual complication of renal biopsy, resulting from marked compression of renal parenchyma by the perinephric haematoma leading to compromise of blood supply to renal micro vasculature. It presents as new onset of hypertension or marked elevation of blood pressure in previously normotensive patients. The phenomenon is usually reversible and responds well with resolution of perinephric haematoma. We here in report a case of Page kidney diagnosed on history and clinical presentation supported by radiological findings and resolution of hypertensive emergency with resolution of haematoma